2022
DOI: 10.1111/jfbc.14453
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin improves pancreatic cancer chemo‐sensitivity by regulating oxidative‐inflammatory networks

Abstract: Chemotherapy is the main method for controlling pancreatic cancer metastasis but the prevalent chemotherapy resistance limits its utilization. The response of oxidation and inflammation often promotes pancreatic cancer progression and chemo‐resistance. It is critical to explore the potential natural products with few side effects to control inflammatory responses and understand the related mechanisms. Quercetin is a flavonoid widely found in numerous vegetables, fruits, and foods and is thought to have antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 125 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…This may explain why the KEGG analysis results showed enrichment in the cancer pathway. [44,45] Atherosclerosis and venous thrombosis were once believed to have entirely distinct pathogenesis. However, recent research has challenged this notion.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the KEGG analysis results showed enrichment in the cancer pathway. [44,45] Atherosclerosis and venous thrombosis were once believed to have entirely distinct pathogenesis. However, recent research has challenged this notion.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing the PPI results, we found that the core targets of eggplant for chilblains were IL-6, TNF, TLR4, CXCL8, and PPARG. Among these, IL-6, TNF, TLR4, and CXCL8 (IL-8) are well-known inflammatory cytokines or chemokines involved in various types of inflammatory responses. , PPARG is a nuclear receptor that binds peroxisome proliferators, which controls the peroxisomal β-oxidation pathway of fatty acids and is the key regulator of adipocyte differentiation and glucose homeostasis . GO enrichment analysis showed that the potential targets of active components in eggplant are mainly distributed in the nucleus and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%